2020
DOI: 10.5751/es-11810-250401
|View full text |Cite
|
Sign up to set email alerts
|

Plantations and pastoralists: afforestation activities make pastoralists in the Indian Himalaya vulnerable

Abstract: Global policies to mitigate climate change and protect forests are increasingly incentivizing the large-scale planting of trees. Yet tree planting poses a potential threat to the well-being of migratory pastoralists who depend on fodder across landscapes. With this research we seek to understand the impact of decades of afforestation activities in Himachal Pradesh, India, on the livelihoods of Gaddi pastoralists who have herded sheep and goats in the Himalayas for generations. Based on interviews with Gaddi he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
(73 reference statements)
1
27
0
Order By: Relevance
“…There are also concerns that where rights are weak, especially around land tenure, NbS may be implemented in the absence of community consent or cause adverse social consequences. Such rights infringements can impede the success and sustainability of interventions (Ramprasad et al, 2020; Scheidel & Work, 2018; Vidal, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are also concerns that where rights are weak, especially around land tenure, NbS may be implemented in the absence of community consent or cause adverse social consequences. Such rights infringements can impede the success and sustainability of interventions (Ramprasad et al, 2020; Scheidel & Work, 2018; Vidal, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…India provides an excellent context to assess the impact of plantations due to its long history of tree planting programs 14,15 , continuing high level commitment to tree planting 16 , prevalence of areas identified as having forest restoration potential 17 , and large number of forest dependent people 18 . Yet recent systematic reviews on tree planting outcomes found no studies from India 12,13 , and the case studies that do exist suggest plantations may fail 19,20 , endanger livelihoods 20,21 , and threaten native forest cover [22][23][24] .…”
Section: Study Sitementioning
confidence: 99%
“…Adaptation at one level may lead to a transformation at another level of the system (Ramprasad et al, 2020). Defining the system boundaries and its normative dimensions allows to overcome the tensions whether a social-ecological change is a transformation or adaptation (Zanotti et al, 2020).…”
Section: Characterizing a Ses In Transitionmentioning
confidence: 99%
“…Early work on SES regime shifts focused on their ecological components (Armitage et al, 2012). Further studies identified the external drivers that impact the SES and the response of communities, including climate change, economic and political regime shifts (Forbes et al, 2009;Ramprasad et al, 2020;Zanotti et al, 2020). However, few empirical studies have considered the effect of social and cultural changes, which are increasingly common through globalization and world-wide economic development, on the agency of individuals and communities to pertain their traditions and activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation